Online purchase intention of electronic goods based on online customer reviews (OCRs) among females in Kuala Lumpur - Afisha Syazrin, Ahmad Sunazneen (2022)
The purpose of this study is to examine the relationship between electronic word-of-mouth (e-WoM), source credibility, perceived risk and trust to online purchase intention of electronic goods based on online customer reviews among females in Kuala Lumpur during the Covid19 Movement Control Order (MCO) 1.0 to MCO 3.0. The questionnaire was distributed online. A total of 389 feedback were received but only 384 feedbacks are usable. The data were analysed using the Statistical Package for Social Science (SPSS) Version 26. The results indicated that all independent variables are significantly and positively related to online purchase intention of electronic goods based on online customer reviews. The most influential variable is perceived risk, followed by e-WoM and trust. Therefore, this study highlighted that online customer reviews does play an important role in enable customer to assess the risk associated with any online purchase.